PENGGUNAAN ANGKA DALAM PEMBENTUKAN KATA BAHASA TULISAN DAN PLAT KENDARAAN - Ni Luh Suriati (Universitas Islam Balitar, 2017)
This study aimed to describe linguistic phenomena on the use of numbers to represent words used in the police number of vehicles. The focus was emphasized in the sociolinguistic contexts as parts of social education using theory of Dell Hymes. The study used content analysis that used documents on policy numbers for cars as sources of data. Data were collected using observation and interview. The study found that trends to use unique numbers generated genuine ideas from young generation. In daily activities, the youth used the jargon-like codes for communication through SMS or written messages to their peers. The numbers represented expression for joke and unique, e.g. M 30 NG (MEONG), D 6161 T (DIGIGIT), and L 38 AY (LEBAY). It is evidence that creativities of young generation to innovate language existed as genuine creativity.